Good Enough for Government Work: The Constitutional Duty to Preserve Forensic Interviews of Child Victims - McGough, Lucy S. (Law and contemporary problems, 2002)
McGough proceeds with the confidence on the premise that a forensic interview of a child by a member of the prosecutorial team offers many opportunities for compromising the reliability of the child's remembered account. A vast volume of research data now exists that documents the conclusion that the forensic interviewing of children is a very delicate, sophisticated, and high-risk enterprise